Automação no controle de um misturador de água utilizado para higienização de ordenhadeiras bovinas - Arnauts, Gilberto Carlos (2015)
The milking hygiene is necessary after use, usually in separate process steps which each require water at different temperatures for proper cleaning. But getting the correct temperature for each step is not so simple to be performed manually on farms. From a hot flow and other cold water, the farmer will need to properly mix the two water flows in order to reach a desired temperature for the cleaning step, and due to temperature fluctuations and flow, the required constant intervention of the same to maintain optimum temperature of the mixture. This work developed a mixer with automatic control of cold water flow, coupled to an electric heating system, with the goal of reaching a final ideal temperature required for the cleaning of milking machines, regardless of temperature fluctuations and flow at the entrance. We compared two control boards, Arduino and the IOIO During the first seconds of system operation, the opening angle of the cold water tap is calculated based on the hot and cold water temperatures. After this is accomplished by gradually adjusting the angle. The temperature was considered to be achieved when reached a maximum desviation of 1 ° C compared to the desired temperature. The system was more satisfactory with the IOIO, since the desired temperature was stabilized at lower average time 24 seconds after system startup